Diagnostic ability and its influenced factors of ultrasound-guided percutaneous pleural needle biopsy diagnosis for malignant pleural mesothelioma - Zhang, Yuxin; Tang, Jiaxin; Zhou, Xinghua; Chen, Wuxi; Zhang, Shiyu; Li, Yuqin; Zhou, Dazhi; He, Liantu; Tang, Qing (Frontiers in Surgery, 2022)
Background Malignant pleural mesothelioma (MPM) is a highly invasive malignant tumor. Ultrasound guidance has the advantages of real-time, convenience and nonradiative. We sought to identify diagnostic value and its influenced factors of ultrasound-guided percutaneous pleural needle biopsy (US-PPNB) for MPM. Methods Patients who underwent US-PPNB between March 2014 and March 2020 and were finally diagnosed with MPM were retrospectively analyzed. We retrospectively analyzed the US-PPNBs pathological results of all patients clinically confirmed as MPM, and divided US-PPNBs into correctly and incorrectly diagnosed groups. Patient, thoracic, and biopsy variables that affected diagnostic accuracy were assessed. All variables significant on univariate analyses were subjected to multivariate logistic regression to identify significant predictors of diagnostic accuracy. We derived cutoffs for all significant continuous variables and used the Mantel–Haenszel test to determine whether the diagnostic accuracy of US-PPNB for MPM increased with pleural thickness. Results In total, 49 patients with clinically confirmed MPM underwent US-PPNB; 37 diagnoses were correct and 12 were incorrect (accuracy = 75.5%). The pleura was significantly thicker in the correctly diagnosed group (p < 0.001). The pleural thickness cutoff was 4.15 mm and diagnostic accuracy increased with pleural thickness grade (p for trend < 0.05). The diagnostic accuracy was significantly higher when 16-G rather than 18-G biopsy needles were used (p < 0.05). Multivariate logistic regression showed that pleural thickness (odds ratio: 17.2, 95% confidence interval: 2.8-104.1, p = 0.002) and needle size (odds ratio: 6.8, 95% confidence interval: 1.0-44.5, p = 0.044) independently predicted diagnostic accuracy. Conclusions US-PPNB afforded high MPM diagnostic accuracy, and pleural thickness and needle size significantly impacted accuracy.